Ketotifen Effect, A Histamine H1 Antagonist and Mast Cell Growth Inhibitor, on Glycerol-induced Acute Renal Failure in Rats - laham, Shaza Anwar Al (Asian Journal of Pharmaceutics (AJP), 2018)
Aim: Investigating the healing effect of Ketotifen, a selective stabilizer of mast cells and a histamine H1 receptor antagonist, on acute renal failure (ARF) model in rat kidney induced by glycerol. Materials and Methods: A renal failure was produced by rats deprived of water for 24 h followed by i.m. injection with 50% (vol/vol) glycerol (10 ml/kg of body weight). After 30 min, Ketotifen was used at a dose of 2 mg/kg for 5 consecutive days. On the 6th day, the rats were sacrificed; blood was obtained for blood urea and creatinine assays. The kidney tissue was used for the determination of reduced GSH levels. Results and Discussion: The results revealed that simultaneous treatment of glycerol with Ketotifen exhibit a normalizing effect on the main indicators of kidney functions, and reduce the glutathione (GSH) concentration significantly, compared to the glycerol-treated group. Conclusions: The anti-inflammatory and antioxidant effects of Ketotifen in treating the ARF are due to its potential to reduce the urea and creatinine, and increase the GSH.